Enhanced High-Rate Performance of Nanosized Single Crystal ε-VOPO4 with Niobium Substitution for Lithium-Ion Batteries. Issue 6 (9th June 2021) - Siu, Carrie; Zuba, Mateusz J.; Zong, Yanxu; Zhou, Hui; Chernova, Natasha A.; Piper, Louis F. J.; Zhou, Guangwen; Whittingham, M. Stanley
Abstract : ε -VOPO4 has the potential to be the next high energy density cathode material for lithium-ion batteries due to its high thermal stability and its ability to reversibly intercalate two full Li +, giving a high discharge capacity of 305 mAh g −1 . However, vanadyl phosphate materials typically experience poor Li + kinetics that impedes the high-rate capability at the high voltage plateau. In this work, we applied niobium substitution to improve the high-rate performance of the 4.0 V plateau of ε -VOPO4 . Elemental analysis and lattice parameter refinements determined that up to 10% Nb can be substituted into ε -VOPO4 without any impurities. TEM and Synchrotron-based EXAFS confirmed that all the substituted samples have Nb in the ε -VOPO4 structure. Electrochemical tests revealed that 1% Nb substitution can deliver a high discharge capacity of ∼300 mAh g −1 without any degradation in cycling behavior by maintaining its nanosized morphology.